(untitled) (Global Journals of Research in Engineering, 2022)
Illumination represents one of the main factors that affect energy consumption on a building this consumption is even more on an office building This study presents quantitative and qualitative data of the south fa ade of an open-plan office in Panama of a building that has a system to regulate internal light To accomplish this several measurements of illuminance in three different sceneries evaluating daylight factor measuring illuminance levels lx and luminance levels with users perception It was concluded that the building requires this system of light control to operate correctly 75 of the participants describe their workplace as comfortable